Studies on the process of recovering low-temperature waste heat from a flue gas in a pilot-scale plant - Szulc Piotr; Tietze Tomasz; Wójs Kazimierz (Chemical and Process Engineering)
This paper presents studies carried out in a pilot-scale plant for recovery of waste heat from a flue gas which has been built in a lignite-fired power plant. The purpose of the studies was to check the operation of the heat recovery system in a pilot scale, while the purpose of the plant was recovery of waste heat from the flue gas in the form of hot water with a temperature of approx. 90 °C. The main part of the test rig was a condensing heat exchanger designed and built on the basis of laboratory tests conducted by the authors of this paper. Tests conducted on the pilot-scale plant concerned the thermal and flow parameters of the condensing heat exchanger as well as the impact of the volumetric flow rate of the flue gas and the cooling water on the heat flux recovered. Results show that the system with a condensing heat exchanger for recovery of low-temperature waste heat from the flue gas enables the recovery of much higher heat flux as compared with conventional systems without a condensing heat exchanger.